Creating an International Baccalaureate Student-friendly National University in Japan - Sabina, Mahmood; Kyosuke, Satake; Masaya, Iizuka; Katsumi, Tanaka; Ichiro, Ueda; Ichiro, Ishii; Makoto, Tahara (Advances in Social Sciences Research Journal, 2018)
The number of International Baccalaureate (IB) students applying to Japanese Universities is increasing. Okayama University is a Super Global Japanese National University which started IB admissions since 2012 and presently, has 36 IB students in 11 faculties and 1 special program. Through IB student support, IB research and conducting surveys, Okayama University is aiming to become an IB friendly University. Twenty college counselors from International Schools and First Article schools in Japan, filled out a survey anonymously, regarding the following topics; expectations of Japanese National Universities; disappointing aspects of Japanese National University Admission policies; suggestions to improve existing admission policies; reasons behind IB students choosing Foreign Universities over Japanese Universities or choosing Private Universities over National Universities, respectively. Lack of understanding of the IB education system, leading to unrealistic expectations of IB students, was a major concern among all college counselors. Unfamiliarity with overseas admission policies regarding age at admission, language requirements, IB credit transfers and recognition of the IB Diploma, led IB students to opt for foreign Universities. Finally, Japanese Private Universities with admission policies similar to overseas Universities, offering a wide range of study options, are prioritized over National Universities, irrespective of high tuition fees. Multiple approaches are necessary to become an IB-friendly University. A clear understanding of the IB education system which is very different from Japanese High School education, is essential. Okayama University is making every effort towards balancing the needs of IB students with the expectations of Japanese University teachers to become more IB friendly.